Feeding and Growth Patterns in Three Freshwater Fishes from River Godavari in Maharashtra (India) - D.K. Hiwarale, P.M. Davne, D.L. Sonwane , Y.K. Khillare, M.V. Gaikwad, T.S. Pathan, S.L. Gaikwad (Recent Research in Science and Technology, 2009)
2865 fresh water fishes i.e. Channa gachua, Labeo kontius and Rasbora daniconius for the period of two years [January 2006 to December 2008] were scanned for the study of growth pattern and feeding habitats. Fishes at fingerling stages, 5cm in length and 3g in weight in R. daniconius, 3cm in length and 2.5 g in weight in C. gachua and 7 cm length and 4.5g in weight in L kontius were collected in the vicinity of river Godavari and reared in laboratory in big [3Ã¢â‚¬â„¢x2.5Ã¢â‚¬â„¢x2] glass aquarium under ambient conditions for a period of 3 months fishes were fed with suitable food [planktons]. In early life stages [fingerling], all fishes were herbivorous and no definite food selectivity was observed. After two months, selection of the food items has been noticed and found continued in their respective feeding habitats. Average feeding rate [0.26%] found in Channa gachua than Labeo kontius [021%] and R. daniconius [0.19%] but on the contrary, average growth rate was more in L .kontius [68%] than C. gachua [49%] and R. daniconius [38%]. Isometric growth was found in all fishes attributing to feeding rate, selectivity and food conversion coefficient in each species. The Metric and Meristic measurement helps to establish certain relationship which later on justifies significantly the growth pattern in the fish. Regression values in C. gachua as growth coefficient, r=0.7288 in R. daniconius r = 0.6897 andÃ‚Â Ã‚Â r = 0.6789 in L. kontius are statistically significant.